1995
DOI: 10.1002/ijc.2910620304
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic influence of neuroendocrine cells in prostate cancer: Results of a long‐term follow‐up study with patients treated by radical prostatectomy

Abstract: The distribution of immunohistochemically defined neuroendocrine (NE) cells in benign, pre-cancerous and neoplastic prostatic tissues and the prognostic value of these cells in prostate cancer were studied in the radical prostatectomy specimens of 90 patients from whom complete long-term follow-up data were available. The tissue blocks containing all the different Gleason patterns observed in a particular tumor were selected and immunostained. Since chromogranin B stained only a few cells compared to chromogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
65
1

Year Published

1997
1997
2006
2006

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(70 citation statements)
references
References 21 publications
4
65
1
Order By: Relevance
“…In accordance with observations made for other markers, 31 we did not find a correlation between PAM or PAMP expression and GSS for either group of RPs or the TURPs. PAMP-or PAMassociated NE differentiation does not appear to be directly associated with tumor grade and, furthermore, does not have clinical value for estimating prognosis.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In accordance with observations made for other markers, 31 we did not find a correlation between PAM or PAMP expression and GSS for either group of RPs or the TURPs. PAMP-or PAMassociated NE differentiation does not appear to be directly associated with tumor grade and, furthermore, does not have clinical value for estimating prognosis.…”
Section: Discussionsupporting
confidence: 92%
“…31 Tissue sections adjacent to slides immunostained for PAMP or PAM were stained with hematoxylin and eosin and the neoplastic zones present in every tissue identified and marked. These marks were copied on the corresponding immunolabeled slides.…”
Section: Quantification Of Immunostaining and Statistical Analysis Ofmentioning
confidence: 99%
“…In the majority of published studies, CgA immunostaining in tumor specimens obtained after radical prostatectomy failed to show a prognostic role (Noordzij et al 1995, Bubendorf et al 1997, Abrahamsson et al 1998, Ahlgren et al 2000, Bostwick et al 2002. Similarly, Lilleby et al (2001) did not show a significant correlation between elevated circulating CgA values and prognosis in a patient subset with hormone-naive disease submitted to radiotherapy.…”
Section: Discussionmentioning
confidence: 96%
“…These findings notwithstanding, the relationship with survival is still controversial, since some studies demonstrated a negative prognostic role (Weinstein et al 1996, McWilliam et al 1997, Theodorescu et al 1997, while others did not (Noordzij et al 1995, Bubendorf et al 1997, Abrahamsson et al 1998, Ahlegren et al 2000, Bostwick et al 2002. All these studies involved hormonenaive patients.…”
Section: Introductionmentioning
confidence: 99%
“…However, we found no significant differences in age, pre-biopsy serum PSA value, Gleason score, EOD grade, T stage or N stage between the Cg A-positive and Cg A-negative groups. Noordzji et al (18) and Isshiki et al (11) also found no significant differences or correlation in Gleason score or pathological stage with NE cell differentiation.…”
Section: Discussionmentioning
confidence: 90%